Effects of bond-coatings on plasma sprayed calciumphosphate coatings - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2003)
In this study the effects of bond-coatings on various calcium phosphate coatings were studied. From human teeth dentine (DFA) and enamel derived fluorapatite (EFA) plasma powders were sprayed on titanium with and without a bond-coating. As control group original hydroxyapatite (HA) powder for biomedical spraying purposes was also used on titanium with and without a bond-coating. Tensile strength tests were performed according to the F-633 ASTM standards. It was observed that bond-coatings had significantly increased the tensile strength values compared to non-bond coatings. It was interesting that the use of a bond-coating did not influence any remarkable tensile strength values compared to original coating values but that the % of micro voids has decreased from 1.11% to 0.29%. This means that a better plasma coating with less micro voids, which could affect the quality of the coating with continuous progress, has been provided. In other words, the use of bond-coatings was found to be very useful. This phenomenon should be investigated in further studies to develop better implant coats.
Keywords: hydroxyapatite; fluorapatite; plasma-spraying; bond-coatings